Legal Analysis of the Application of Standard Clauses in Banking Agreements and Their Legal Consequences - Fitrianto, Bambang (Faculty of Law, Universitas Pekalongan, 2024)
The use of standard clauses in an agreement is based on the needs that exist in society. The purpose of making a standard agreement at the Bank is to provide practicality to the parties so as to facilitate and save time in transactions. However, the absence of customer involvement in the preparation of the standard agreement puts the customer in a weak position. In this case the customer does not have the opportunity to negotiate it so that he only has the choice to accept or reject it. However, the standard agreement will only apply if the consumer is willing to obey and submit to any provisions prepared by the business actor. The purpose of this research is to see the legal consequences of banks in the inclusion of standard clauses and the prudential principles of banks in the inclusion of standard clauses in the agreement. The method used in this thesis is normative juridical research, with data collection by library research and related laws and regulations. Based on the results of the research conducted, the form of agreement at the Bank is usually set in a standard form, based on the essence of the agreement, the parties involved have rights and obligations in creating the desired legal relationship. Standard clauses are allowed as long as the contents do not lead to an exoneration clause. In other words, the condition of exoneration is “a condition that specifically relieves the employer from responsibility for adverse consequences arising from the execution of the agreement. An agreement must be executed in good faith”. This means that in every agreement, basically all parties are free in determining the contents of the agreement, deciding with whom to make an agreement, but it must always be based on the principle of good faith, not violating laws and regulations, and not violating the interests of the community. This aims to achieve justice for the parties to the agreement so that there is no exploitation of the weak party.